Host Defense Peptide LL-37-Mediated Chemoattractant Properties, but Not Anti-Inflammatory Cytokine IL-1RA Production, Is Selectively Controlled by Cdc42 Rho GTPase via G Protein-Coupled Receptors and JNK Mitogen-Activated Protein Kinase - Hemshekhar, Mahadevappa; Choi, Ka-Yee Grace; Mookherjee, Neeloffer (Frontiers in Immunology, 2018)
The human host defense peptide LL-37 promotes immune activation such as induction of chemokine production and recruitment of leukocytes. Conversely, LL-37 also mediates anti-inflammatory responses such as production of anti-inflammatory cytokines, e.g., IL-1RA, and the control of pro-inflammatory cytokines, e.g., TNF. The mechanisms regulating these disparate immunomodulatory functions of LL-37 are not completely understood. Rho GTPases are GTP-binding proteins that promote fundamental immune functions such as chemokine production and recruitment of leukocytes. However, recent studies have shown that distinct Rho proteins can both negatively and positively regulate inflammation. Therefore, we interrogated the role of Rho GTPases in LL-37-mediated immunomodulation. We demonstrate that LL-37-induced production of chemokines, e.g., GRO-α and IL-8 is largely dependent on Cdc42/Rac1 Rho GTPase, but independent of the Ras pathway. In contrast, LL-37-induced production of the anti-inflammatory cytokine IL-1RA is not dependent on either Cdc42/Rac1 RhoGTPase or Ras GTPase. Functional studies confirmed that LL-37-induced recruitment of leukocytes (monocytes and neutrophils) is also dependent on Cdc42/Rac1 RhoGTPase activity. We demonstrate that Cdc42/Rac1-dependent bioactivity of LL-37 involves G-protein-coupled receptors (GPCR) and JNK mitogen-activated protein kinase (MAPK) signaling, but not p38 or ERK MAPK signaling. We further show that LL-37 specifically enhances the activity of Cdc42 Rho GTPase, and that the knockdown of Cdc42 suppresses LL-37-induced production of chemokines without altering the peptide’s ability to induce IL-1RA. This is the first study to demonstrate the role of Rho GTPases in LL-37-mediated responses. We demonstrate that LL-37 facilitates chemokine production and leukocyte recruitment engaging Cdc42/Rac1 Rho GTPase via GPCR and the JNK MAPK pathway. In contrast, LL-37-mediated anti-inflammatory cytokine IL-1RA production is independent of either Rho or Ras GTPase. The results of this study suggest that Cdc42 Rho GTPase may be the molecular switch that controls the opposing functions of LL-37 in the process of inflammation.